Dilutional coagulopathy in pediatric scoliosis surgery: A single center report. Issue 11 (8th October 2018) - Baker, Courtney E.; Marvi, Tanya; Austin, Thomas M.; Payne, Shelby; Mignemi, Megan E.; Gailani, David; Wheeler, Allison P.; Nguyen, Thanh T.; Lovejoy, Steven A.; Martus, Jeffrey E.; Mencio, Gregory A.; Schoenecker, Jonathan G.
Summary: Background: Children undergoing posterior spinal fusion experience high blood loss often necessitating transfusion. An appropriately activated coagulation system provides hemostasis during surgery, but pathologic dysregulation can cause progressive bleeding and increased transfusions. Despite receiving antifibrinolytics for clot stabilization, many patients still require transfusions. Aims: We sought to examine the association of dilutional coagulopathy with blood loss and blood transfusion in posterior spinal fusion for pediatric scoliosis patients. Methods: A retrospective, single institution study of children undergoing posterior spinal fusion >6 levels with a standardized, prospective anesthetic protocol utilizing antifibrinolytics. Blood loss was evaluated using a hematocrit‐based calculation. To evaluate transfusions, a normalized Blood Product Transfusion calculation was developed. Factors associated with blood loss and blood transfusions were determined by univariate analysis and multivariate regression modeling with multicollinearity and mediation analysis. Results: Patients received 73.7 mL/kg (standard deviation ±30.8) of fluid poor in coagulation factors. Estimated blood loss was 42.6 mL/kg (standard deviation ±18.0). There was a significant association between estimated blood loss and total fluids delivered (Spearman's rho = 0.51, 95% confidence interval 0.33‐0.65, P < 0.001). Factors significantly associated with normalized Blood Product Transfusion in this cohort included age, weight, scoliosis type, levels fused, total osteotomies, pelvic fixation, total fluid, maximum prothrombin time, and minimum fibrinogen. Regression modeling showed the best combination of variables for modeling normalized Blood Product Transfusion included patient weight, number of levels fused, total fluid administered, and maximum prothrombin time. Conclusion: Blood product transfusion remains a frustrating problem in pediatric scoliosis. Identifying and controlling dilutional coagulopathy in these patients may reduce blood loss and the need for blood transfusion.